The initiation mechanism and distribution rule of wheel high-order polygonal wear on high-speed railway. (January 2021) - Ma, Chaozhi; Gao, Liang; Cui, Rixin; Xin, Tao
Highlights: The OOR growth rate evaluating whether each-order polygon grows or not is proposed. The rail 3 rd -order bending resonance between bogie wheels causes polygon initiation. The rail bending resonances between adjacent-bogie wheels intensify polygon growth. Explaining why polygons frequently emerge in summer and in the 1 st /4 th wheelset. Abstract: The wheel high-order polygonal wear leads to strong vibration/ noise and deterioration of railway systems, whose distribution is closely related to the seasonality and wheelset position. To elucidate its initiation mechanism and distribution rule, a multi-vehicle-track coupled dynamic model considering the wheel-rail variable friction characteristics was established and the OOR growth rate used to evaluate the degree of polygonal wear initiation was proposed. The wheel-rail resonance and OOR growth rate was simulated, and compared with the results under the single/ double/ multiple wheelset-rail interactions. We find that the rail bending modes between wheels of bogie are the key to induce friction power resonance and polygonal wear initiation, in which the rail 3rd-order bending resonance between wheels of bogie is the root cause of the high-order polygonal wear. The rail bending resonance between wheels of adjacent bogies accelerates the further growth of polygonal wear. Furthermore, by analyzing the influence of wheel-rail friction coefficient, fastener stiffness, and curve track on the polygonal wear, the distribution rule related to the seasonality and wheelset position was explained. The polygonal wear is more frequent and severe in summer than in other seasons, mainly due to frequent rainfalls, followed by high temperatures. The 1st /4th wheelset is prone to form the polygonal wear, which is due to the vehicle reciprocates on the railway line containing curves and the rail bending resonance between wheels of adjacent bogies. The research is expected to provide guidance for the prevention and service of polygonal wear.